Usage and satisfaction of religious websites among students in IIUM - Aripin, Syaima'a; Wok, Saodah (Penerbit Universiti Sains Islam Malaysia, 2016)
Websites have been the source of information for most students in search of knowledge. The students of International Islamic University Malaysia (IIUM), especially, need to search for information from the Islamic websites in relation to their studies. As such, this study tries to assess the degree of religious website usage among students and their satisfaction in using them. The objectives of the study are (1) to determine the level of usage, awareness, perception, attitude and behavior of using the Islamic websites; (2) to assess the level of satisfaction in using the Islamic websites; and (3) to analyze the relationships between satisfaction and usage, awareness, perception, attitude and behavior in using the Islamic websites. The study uses a quantitative research design, employs the survey method and uses the questionnaire as the instrument for data collection. Results show that students use the general websites more often than the religious websites. The students are aware of the religious websites and have a positive perception and attitude towards the religious websites. They also use the religious websites for their own benefit and are satisfied with the religious websites presentation and content. Their satisfaction is positively correlated with awareness, perception, attitude and behavior in using the religious websites.